Vertigo and Dizziness from Environmental Motion: Visual Vertigo, Motion Sickness, and Drivers' Disorientation - Bronstein, Adolfo M.; Golding, John F.; Gresty, Michael A. (Seminars in Neurology, 2013)
The normal vestibular system may be adversely affected by environmental challenges which have characteristics that are unfamiliar or ambiguous in the patterns of sensory stimulation they provide. A disordered vestibular system lends susceptibility even to quotidian environmental experiences as the sufferer becomes dependent on potentially misleading, nonvestibular sensory stimuli. In both cases, the sequelae may be vertigo, incoordination, imbalance, and unpleasant autonomic responses. Common environmental motion conditions include visual vertigo, motion sickness, and motorists' disorientation. The core therapy for visual vertigo, motion sickness, and drivers' disorientation is progressive desensitization within a cognitive framework of reassurance and explanation, plus anxiolytic tactics and autogenic control of autonomic symptoms.
Keywords: motion sickness; vestibular; visual motion; driving